The change in plasma GABA, glutamine and glutamate levels in fluoxetine- or S-citalopram-treated female patients with major depression - GÖREN, MEHMET ZAFER (SPRINGER HEIDELBERG, 2009)
Objective The aim of this study was to investigate the relationship between plasma glutamate, glutamine and gamma-aminobutyric acid (GABA) levels in female patients with major depression treated with S-citalopram or fluoxetine. Methods The patients were assigned into S-citalopram (10 mg/day) or fluoxetine (20 mg/day) groups (n= 15 per group). The Hamilton and Beck Depression Inventory Scales were performed on all study participants, and blood samples were collected. The same procedures were repeated 10 days following the onset of therapy. Fifteen female healthy volunteers were also included in the study for the evaluation of normal plasma levels. Results The plasma GABA levels of the healthy volunteers were higher whereas those for glutamate and glutamine were lower than the day zero samples of the patients. An increase in plasma GABA levels and a decrease in glutamate and glutamine levels were observed on the 10th day of treatment. No difference was detected between the drug treatments. Conclusion Our findings may suggest that GABA, glutamate and glutamine play a role in depression and that plasma GABA may be used as a biomarker for treatment control.
Keywords: Antidepressant therapy; Biomarker; SSRI; Therapy control; GAMMA-AMINOBUTYRIC-ACID; PERFORMANCE LIQUID-CHROMATOGRAPHY; RAT CEREBRAL-CORTEX; MOOD DISORDERS; ELECTROCONVULSIVE-THERAPY; SULFITE DERIVATIZATION; PREFRONTAL CORTEX; RECEPTOR CHANNELS; CINGULATE CORTEX; RAPHE NUCLEI